Benefits of Prostrate Position and Coughing Exercises in the Management of Cardiopulmonary Parameters Alteration among Patients with COVID-19 - Haider Nawaf Abed-Ali, Hassan Abdullah Athbi (Pakistan Journal of Medical & Health Sciences, 2022)
Method: A sixty patients with COVID-19 were randomly selected to conduct an experimental study to investigate the benefits of prostrate position and coughing exercises upon cardiopulmonary parameters among non-intubated patients with COVID-19. Results: two-thirds of participants were ˃60 years old, 60% and 46.7% of the experimental and control group respectively were males, 36.7% of participants did not have any chronic diseases, but asthma was present in a third of them. The bilateral-peripheral and central area was the affected part of the lung in more than 40% of patients. More than 45% of the lung volume was affected in 80% of the experimental group and 50% of the control group. Finally, 96.7% of the experimental group and 90% of the control group did not take the COVID-19 vaccine. Furthermore, a statistically significant difference was found between the mean of cardiopulmonary parameters for the experimental group, while there was no statistical significance difference that was shown in the control group. Conclusion: the application of prostrate position and coughing exercises have a positive effect on improving cardiopulmonary parameters among COVID-19 patients lasting for more than four hours.